Evaluation of the Student’s Parents about the School Milk Programme: The Case of Isparta - Gözde Altındal; Mevlüt Gül; Pelin Ertan (Turkish Journal of Agriculture: Food Science and Technology)
In this study, it was aimed to determine the approaches of primary school students’ parents participating in the school milk programme in the Isparta province. The data obtained by the questionnaire method were used from 359 students’ parents who were included in the school milk programme. The families were divided into four groups according to the household income. It was determined that the families consumed more pasteurized milk. The average age of the interviewed individuals was 37.14 years. About 36.21% of the parents were high school graduates. 53.48% of them spend money on milk less than 50 TL. Household size was 4.05 persons. 21.84% of them consume milk hot. The attitude of the parents to the school milk programme was generally positive (82.17%). The school milk programme was believed to be a habit of consuming milk. It was found that 33.33% of the surveyed parents were negative about the school milk programme because they did not trust the content of the milk distributed. In the study, 49.30% of the parents thought that the school milk programme increased the milk consumption habits of the children and 67.97% thought that there was not more supply of milk distributed. For the purpose of implementing the school milk programme, 48.75% of the families had a judge to love the milk and make milk drinking habit. The majority of the families (62.40%) were preferred daily milk in the products distributed and 44% believed that drinking milk was subjected to nutritional analysis. It is suggested that the Ministry of National Education and the Ministry of Health should inform families about the benefits of milk and school milk programme.